Bridging the gap: Aligning human resource theory and practice - Linde, Bennie; Schalk, René (Human resource management review, 2026)
This special issue of Human Resource Management Review addresses the enduring divide between human resource (HR) theory and practice, building on the theme of the HR Division International Conference (HRIC2023), Bridging the gap: Aligning human resource theory and practice. The collection highlights conceptual and contextual sources of this gap, including the decontextualised use of Western-derived HR models, challenges in translating theory into practice-based tools, neglect of Global South contexts, and weak integration of practice-based evidence into theoretical frameworks. Drawing on comparative institutionalism, implementation research, and decolonial perspectives, the editorial outlines how HRM practices operate as mediating mechanisms between legal frameworks, collective rights, and workplace realities, shaping outcomes such as economic development, labour peace, workplace democracy, and social justice. Six articles included in the special issue provide complementary perspectives: leadership in times of crisis, hybrid scholar–practitioner roles, co-creation in research, HR practitioners as brokers, inclusive approaches to talent management, and the psychological impact of HR analytics. Together, these contributions demonstrate pathways for strengthening construct clarity, implementation fidelity, and contextual relevance, while promoting more inclusive, globally representative HR knowledge. By foregrounding both theoretical innovation and practice-based insights, this special issue advances a dual agenda: to refine HRM theory through engagement with practice, and to enhance practice through evidence-informed, contextually sensitive research. Ultimately, bridging the theory–practice gap requires institutional innovation, methodological rigour, and sustained collaboration between scholars and practitioners.